Postharvest investigations into chlorophyll fluorescence and low temperature injury in cut roses (Rosa hybrida L.) - Pompodakis, Nektarios E. (Cranfield University, 2005)
This is one of the first studies on the relationship between pre-harvest environmental conditions found in the Mediterranean and postharvest characteristics of cut roses (Rosa hybrida L. ). Effects of storage temperature on vase life parameters were also studied for roses grown all year round. The postharvest storage of roses at low temperature is a useful practice, in terms of market flow regulation. However, a reduction in vase life and loss of flower quality has been recorded after storage due to Low Temperature Injury (LTI). LTI of roses is difficult to assess by visual observation. Relative chlorophyll fluorescence (F'IFR, ), which is a non-invasive technique that provides an index of stress effects on photosystem II (PS II) activity, was used to investigate LTI in roses. The plant growth regulator abscisic acid (ABA) can cause physiological responses that protect plants against CI or LTI. The overall objectives of this study were firstly to evaluate the pre-harvest environmental conditions affecting vase life and secondly to evaluate novel potential ABA treatments to protect cut roses against LTI. Vase life durations and Fv. /Fm ratios measured after low temperature storage for `First Red' and `Akito' roses were seasonally dependant. Vase lives of roses grown during winter were significantly (P _< 0.001) shorter compared to roses grown during the rest of the year. In autumn and winter experiments F.. IF.. ratios were generally reduced following storage at 1°C, suggesting LTI of roses. Thus, the fall of F,. /Fm was due to an interaction of growing season and storage at I. T. However, in second year experiments, growing temperature and PFD were relatively higher and, as a result, Fý/Fm did not decline for `Akito' roses after low temperature storage, indicating a strong influence of environmental conditions. Higher PFD and temperature glasshouse during the year were positively and significantly correlated with maintenance of post-storage Fv. /Fm ratios and longer vase life. It is suggested that shorter vase lives and lower post-storage FV/Fm values after storage at 1°C are consequences of reduced photosynthesis and smaller carbohydrate pools in winter- harvested roses. Because of the lack of correlation between Fv. /Fm and post-storage vase life, it is concluded that the CF parameter F,. /Fm is not a practical index for assessing LTI in cold-stored roses. Growing roses in autumn and winter months increased flower blueing in red petals of `First Red' roses and prevented flower opening for both cultivars. ABA applied as pulse treatment before storage or as vase solution during vase life generally improved vase life parameters. Pulsing `Akito' roses with 10-1 M ABA before storage increased vase life and inhibited bent neck incidence. Also, the presence of ABA in vase solution increased vase life after storage at 1°C, reducing vase solution usage during vase life. Similarly, the synthetic ABA analogue PBI-365, as vase solution ingredient, was effective in extending vase life and reducing transpiration rates in roses after low temperature storage. Increased ABA levels were detected in leaves and petals using HPLC when roses were treated with exogenous ABA before storage and during vase life. Thus, it was assumed that ABA or PBI-365 acted on guard cells by causing stomatal closure. Electrolyte leakage and lipid peroxidation, measured after storage at 1°C, were markedly reduced by application of ABA. Both pulse ABA treatment and vase solutions containing ABA helped to recover F,, /Fm during vase life. Moreover, addition of PBI-365 in vase solution reduced the degree of lipid peroxidation in leaves and petals after storage at 1°C. These observations indicated a protection role of ABA against LTI for roses, which has also been observed in other crops. Further research at the cellular and/or molecular level may help in better understanding the physiological responses of roses to seasonal variation during the year and LTI. In addition, work is also required to look at the ABA and PBI-365 mode of action in roses. Additional research using a wide range of ABA concentrations and assays using exogenous radio-labelled ABA may help to better understand the nature of ABA efficacy.